Galectin-9 protects humanized-ACE2 immunocompetent mice from SARS-CoV-2 infection - Yeung, Stephen T.; Premeaux, Thomas A.; Du, Li; Niki, Toshiro; Pillai, Satish K.; Khanna, Kamal M.; Ndhlovu, Lishomwa C. (Frontiers in Immunology, 2022)
SARS-CoV-2 remains a global health crisis even with effective vaccines and the availability of FDA approved therapies. Efforts to understand the complex disease pathology and develop effective strategies to limit mortality and morbidity are needed. Recent studies reveal circulating Galectin-9 (gal-9), a soluble beta-galactoside binding lectin with immunoregulatory properties, are elevated in SARS-CoV-2 infected individuals with moderate to severe disease. Moreover, in silico studies demonstrate gal-9 can potentially competitively bind the ACE2 receptor on susceptible host cells. Here, we determined whether early introduction of exogenous gal-9 following SARS-CoV-2 infection in humanized ACE2 transgenic mice (K18-hACE2) may reduce disease severity. Mice were infected and treated with a single dose of a human recombinant form of gal-9 (rh-gal-9) and monitored for morbidity. Subgroups of mice were humanely euthanized at 2- and 5- days post infection (dpi) for viral levels by plaque assay, immune changes measures by flow cytometry, and soluble mediators by protein analysis from lung tissue and bronchoalveolar Lavage fluid (BALF). Mice treated with rh-gal-9 during acute infection had improved survival compared to PBS treated controls. At 5 dpi, rh-gal-9 treated mice had enhanced viral clearance in the BALF, but not in the lung parenchyma. Increased T and dendritic cells and decreased neutrophil frequencies in the lung at 5 dpi were observed, whereas BALF had elevated levels of type-I interferons and proinflammatory cytokines. Results suggest a role for rh-gal-9 in limiting acute COVID-19. Further studies are required to determine the optimal design of gal-9 treatment to effectively ameliorate disease.